Good corporate governance improves banking financial performance - Fitrianingsih, Dwi; Sulistiana, Indra (International Journal of Applied Finance and Business Studies, 2024)
This study aims to determine (1) the effect of Institutional Ownership on the Financial Performance of Go Public Banks listed on the IDX, (2) the influence of the Independent Board of Commissioners on the Financial Performance of Go Public Banks listed on the IDX, (3) the influence of the Audit Committee on the Financial Performance of Go Public Banks listed on the IDX. The population of this study is all public banks listed on the Indonesia Stock Exchange for the 2018-2022 period, totaling 43 banks. Sample selection through purposive sampling method. There were 27 banking companies that met the criteria as a research sample so that the research data amounted to 135. The data analysis technique used is descriptive statistics. The results of this study show that Institutional Ownership has a positive and significant effect on Banking Financial Performance. The Board of Independent Commissioners has an insignificant positive effect on the Financial Performance of the Banks. The Audit Committee has an insignificant positive effect on Banking Financial Performance